Voluntary disclosure schemes for offshore tax evasion - Matthew Gould; Matthew D. Rablen (Institute for Fiscal Studies (IFS), 2018)
Tax authorities worldwide are implementing voluntary disclosure schemes to recover tax on offshore investments. Such schemes are typically designed retrospectively following the bulk acquisition of information on offshore holdings, such as the recent "Paradise" and "Panama" papers. They offer an opportunity for affected taxpayers to make a voluntary disclosure, with reduced fine rates for truthful disclosure. We characterize the taxpayer/tax authority game with and without a scheme and show that a scheme increases net expected tax revenue, decreases illegal offshore investment, increases onshore investment, and could either increase or decrease total offshore investment (legal plus illegal).
Keywords: H26; D85; 330; voluntary disclosure; offshore tax evasion; tax amnesty; third-party information